(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
U. of K. J. Vet. Med. Anim. Prod., Vol. 5, Issue 2 (2014) p 66-73ISSN: 24345666Effect of feeding urea-treated groundnut hulls (silage) and molassesduring summer season on carcass characteristics of Desert lambs(Hammari subtype) under range conditionAbdelbagi Ballal Ahmed1, Ikhlas Ahmed Nour2; Ibrahim Musa Tibin3; Omer Mustafa41 Abstract: The study was conducted at Elnuhood Desert Sheep Research Station, NorthKurdofan State, Sudan, during late summer season; to evaluate the effect of supplementationof urea-treated groundnut hulls silage and molasses on slaughter weight and carcasscharacteristic of desert lamb Hammari ecotype. The duration of the experiment was 90 days,60 lambs (thirty males + thirty females) of 6 months average age and 23.4 kg average liveweight were divided into three equal groups(A,B, and C) of twenty lambs(10 males + 10females) each. Groundnut hulls treated with 5 % urea (of its weight) was ensiled for 30 days.Animal in group (A) and (B) were offered a diet composed of 77% treated groundnut hullsand 23 % molasses, while Group C was un -supplemented (the control) . All the groups wereleft to graze in the same way practiced by the nomads in the area. Slaughter weights, carcassweights, composition yield and non carcass components were determined. Supplementationhad higher values for slaughter weight, hot and cold carcass weight, empty body weight, gutfill weight, subcutaneous fat thickness, eye muscle area and dressing percentage but thedifferences were not significant (p>0.05) compared to the free grazing un supplementedgroup( C control). Subcutaneous fat thickness, dressing percentage, leg and loin cuts, totalmuscle , total fat and trims were not significantly different among the groups but the meat:bone ratio was significantly higher in group A (2.4). Group A had the heaviest cuts thangroup B and C. Non carcass components were not significantly (p>0.05) different among thegroups except for empty rumen and reproductive organs. Wholesale cuts weights increasedbut not significant (P>0.05) with increasing the dietary supplementation. Body fat depots ofthe supplemented lambs especially group A was increased compared with the un-supplemented group which had thinner subcutaneous fat cover.Key words: urea, groundnut hulls, silage, grazing, lamb carcass